2011
DOI: 10.2174/1874440001105010040
|View full text |Cite
|
Sign up to set email alerts
|

Brain SPECT Imaging in Complex Psychiatric Cases: An Evidence-Based, Underutilized Tool

Abstract: Over the past 20 years brain Single Photon Emission Computed Tomography (SPECT) imaging has developed a substantial, evidence-based foundation and is now recommended by professional societies for numerous indications relevant to psychiatric practice. Unfortunately, SPECT in clinical practice is utilized by only a handful of clinicians. This article presents a rationale for a more widespread use of SPECT in clinical practice for complex cases, and includes seven clinical applications where it may help optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 58 publications
0
34
0
2
Order By: Relevance
“…Depending on the tracer used, SPECT imaging can be useful for studying cerebral blood flow (CBF), dopamine transporter function, serotonin transporter function, as well as other processes [15]–[17]. Several studies have also shown that SPECT imaging of CBF can be helpful in TBI patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the tracer used, SPECT imaging can be useful for studying cerebral blood flow (CBF), dopamine transporter function, serotonin transporter function, as well as other processes [15]–[17]. Several studies have also shown that SPECT imaging of CBF can be helpful in TBI patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Employing alternative medical treatments, such as Holographic Kinetics, as most depression can be cleared in a few sessions, with Holographic Kinetics, this simply could give more options that are desperately needed to treat veterans affected by PTSD, depression and suicidal ideations. Further research is needed to scientifically measure the efficacy and effectiveness of this non invasive holistic mental health modality on a larger scale [47].…”
Section: Resultsmentioning
confidence: 99%
“…[149][150][151][152][153][154] Standard neuroimaging with computed tomography (CT) or magnetic resonance imaging (MRI) is negative in concussion but are used to evaluate for more serious brain injury. 4,95 Computer tomography is best used acutely for evaluating for bony fracture and for intracranial bleeding, contusion, mass effects, and/or brain stem herniation, whereas MRI is more sensitive for evaluating persistent or worsening symptoms or concern for underlying pathology (eg, headache or seizure disorder, arteriovenous malformation, Chiari malformation, etc).…”
Section: Neuroimagingmentioning
confidence: 99%